Sedao Capitalism: Growth of Sakai Entrepreneurs in Duri Riau - Justicio, Muhammad Deckaryan Lexa; Amady, M. Rawa El (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study concerns the growth of Sakai entrepreneurs in Pematang Pudu Village, Duri, Riau. It is the only study that discusses the customary-law community growth in Indonesia. Thus, it has an extremely strong novelty. Since the reformation, the Sakai tribes in Pematang Pudu have owned 21 contracting companies that worked on the projects of PT. Chevron Pacific Indonesia. Then, they also had an integrated agricultural complex that was modernly managed by involving a college and the government of Bengkalis district. This study used an ethnographic design where the researcher was on the research’s site for more than two months and lived with the community. The researcher was also involved in in-depth observations and interviews with informants who were selected based on their positions in GAPENSI, integrated agriculture, and traditional leaders. Data obtained were validated and decoded. And they were analyzed qualitatively and written descriptively. This study found that Sakai entrepreneurs in Pematang Pudu were grown by Chevron through the LBD program like affirmative action, and the growth of these entrepreneurs was based on kinship, so that entrepreneurs came from a big family. It could be said that Sakai entrepreneurs in Pematang Pudu were sedao capitalism or close relative capitalism. This study contributed to economic anthropology by introducing the concepts of sedao capitalism and development anthropology that stated social planning was necessarily involved the wider community in the decision-making. This study can be used by the government and companies related to CSR programs while carrying out social planning for the community.